2011
DOI: 10.1111/j.1600-0714.2010.01003.x
|View full text |Cite
|
Sign up to set email alerts
|

miR‐181 as a putative biomarker for lymph‐node metastasis of oral squamous cell carcinoma

Abstract: miR-181 may enhance lymph-node metastasis through regulating migration, which could potentially be exploited as a putative biomarker for patients with OSCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
78
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(84 citation statements)
references
References 30 publications
3
78
0
3
Order By: Relevance
“…To date, certain miRNAs have been suggested to play significant roles in OSCC development (9,(20)(21)(22)(23), which may function alone or in a cooperative manner for OSCC development. The overexpression of oncogenic miRNA may reduce the levels of the protein products of tumor-suppressor genes.…”
Section: Discussionmentioning
confidence: 99%
“…To date, certain miRNAs have been suggested to play significant roles in OSCC development (9,(20)(21)(22)(23), which may function alone or in a cooperative manner for OSCC development. The overexpression of oncogenic miRNA may reduce the levels of the protein products of tumor-suppressor genes.…”
Section: Discussionmentioning
confidence: 99%
“…There was a weakly positive correlation between the tissue and serum levels of miR-544. The majority of previous studies have demonstrated the same trend of alteration between circulating miRNAs and tissue miRNAs, either an increase or decrease, in various types of cancer (24)(25)(26). However, a different correlation between circulating miRNAs and tissue miRNAs has also been observed.…”
Section: Discussionmentioning
confidence: 86%
“…In addition, patients with higher levels of miR-181 were more likely to show lymph node metastasis, vascular invasion by tumor cells, and poor prognosis (Yang et al, 2011). As a member of the miR-181 family, miR-181b also may play a role in the variation in tumorigenesis among different cancers, and its decreased expression is inversely correlated with increased protein levels of the myeloid cell leukemia sequence 1-and B-cell lymphoma 2-targeted genes (Ji et al, 2009;Chen et al, 2010).…”
Section: Discussionmentioning
confidence: 99%